Purification and Characterization of the tricarboxylate carrier from Eel liver mitochondria - V. ZARA; L. SICULELLA; G. GNONI AND F. PALMIERI; IACOBAZZI, Vito (1996)
The tricarboxylate carrier from eel (Anguilla anguilla) liver mitochondria was solubilized with Triton X-100 and purified by sequential chromatography on hydroxyapatite and Matrex Gel Blue B. On SDS-polyacrylamide gel electrophoresis, the purified fraction showed a single polypeptide band with an apparent molecular mass of 30.4 kDa. When reconstituted into liposomes, the tricarboxylate transport protein catalyzed a very active 1,2,3-benzenetricarboxylate-sensitive citrate/citrate exchange. It was purified 641-fold with a recovery of 13.3% and a protein yield of 0.02% with respect to the mitochondrial extract. The properties of the reconstituted carrier, i.e., requirement for a counteranion, substrate specificity and inhibitor sensitivity, were similar to those of the tricarboxylate carrier purified from rat liver mitochondria. These studies provide the first information on the mitochondrial tricarboxylate transport protein of a fish